2020
DOI: 10.1155/2020/8781674
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Value of the Pretreatment Systemic Immune-Inflammation Index in Patients with Colorectal Cancer

Abstract: Background. Multiple studies have reported the significance of the systemic immune-inflammation index (SII) in the prognosis of colorectal cancer (CRC), but no consensus has yet been reached. The purpose of this study was to systematically assess the prognostic value of SII in patients with CRC. Materials and Methods. We performed a systematic literature search in PubMed, Embase, and the Cochrane Library for eligible studies. The correlation between pretreatment SII and overall survival (OS), disease-free surv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 41 publications
2
4
0
Order By: Relevance
“…Elevated SII index scores indicate elevated platelets and neutrophils, and decreased lymphocytes. CRC patients are prone to infection, recurrence, or metastasis after surgery, which ultimately leads to a poor prognosis, and previous studies have confirmed that an increased SII index score is the main risk factor for the poor postoperative prognosis of CRC patients, which supports the findings of this study ( 16 - 20 ). However, compared to previous studies, this study is somewhat innovative; we did not find any other study that explored the relationship between the SII index and postoperative infectious complications in CRC patients, and this study confirmed that an increased SII index score indicates an increased incidence of postoperative infectious complications.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Elevated SII index scores indicate elevated platelets and neutrophils, and decreased lymphocytes. CRC patients are prone to infection, recurrence, or metastasis after surgery, which ultimately leads to a poor prognosis, and previous studies have confirmed that an increased SII index score is the main risk factor for the poor postoperative prognosis of CRC patients, which supports the findings of this study ( 16 - 20 ). However, compared to previous studies, this study is somewhat innovative; we did not find any other study that explored the relationship between the SII index and postoperative infectious complications in CRC patients, and this study confirmed that an increased SII index score indicates an increased incidence of postoperative infectious complications.…”
Section: Discussionsupporting
confidence: 91%
“…In patients with malignant tumors, neutrophils are inflammatory cells that indicate that the patient's systemic level of inflammation is increased, which is conducive to the local tissue angiogenesis of tumors, which in turn promotes the proliferation and metastasis of CRC cells (13). Additionally, this systemic inflammation also promotes an increase in intestinal permeability, which in turn leads to the studies have confirmed that an increased SII index score is the main risk factor for the poor postoperative prognosis of CRC patients, which supports the findings of this study (16)(17)(18)(19)(20). However, compared to previous studies, this study is somewhat innovative; we did not find any other study that explored the relationship between the SII index and postoperative infectious complications in CRC patients, and this study confirmed that an increased SII index score indicates an increased incidence of postoperative infectious complications.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Recently, it has been reported that the SII sore is of prognostic value in many malignant tumor types including hepatocellular carcinoma [ 37 ], gastric cancer [ 38 ], colorectal cancer [ 39 ], and urological and gynecological tumors [ 13 , 40 ]. Given that RCC is an inflammatory disease, the investigation of the SII score seems to be of particular interest in patients treated with immune checkpoint inhibitors.…”
Section: Discussionmentioning
confidence: 99%
“…The SII has been reported as a useful prognostic indicator in many solid tumors, including gallbladder ( 31 ), pancreatic ( 13 ), and colorectal cancer ( 32 ), as well as in intrahepatic cholangiocarcinoma ( 33 ). Studies have investigated the association between SII and survival outcomes in patients with RCC ( 18 25 , 29 , 30 ); however, the results remain controversial.…”
Section: Discussionmentioning
confidence: 99%